2012
DOI: 10.1016/j.solmat.2011.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Growth of N-substituted polypyrrole layers in ionic liquids: Synthesis and its electrochromic properties

Abstract: A new series of pyrrole family, N-substituted phenyl attached alkyl at the ortho, meta and para position were synthesized by a straight forward method and were exploited as an innovative monomer for electroactive polymers. Ionic liquids were employed as a medium for electro-polymerization of these monomers to obtain N-(methyl)phenyl polypyrroles. N-substituted polypyrroles show different morphologies and conductivity according to position of methyl group on the benzene ring and synthesis medium. The electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Additionally, it is observed that the FTIR spectrum of OMDPP displays small changes compared with that of the monomer MDPP. The peak at 732 cm À1 , corresponding to the CÀ ÀH bonds from the pyrrole ring [14], seems slightly weaker. It indicates that the pyrrole ring of the monomer coupled partially.…”
Section: Structure Characterization Of Omdppmentioning
confidence: 95%
“…Additionally, it is observed that the FTIR spectrum of OMDPP displays small changes compared with that of the monomer MDPP. The peak at 732 cm À1 , corresponding to the CÀ ÀH bonds from the pyrrole ring [14], seems slightly weaker. It indicates that the pyrrole ring of the monomer coupled partially.…”
Section: Structure Characterization Of Omdppmentioning
confidence: 95%
“…), [24][25][26][27][28][29][30][31][32][33][34][35] Prussian blue, [36] conducting polymers (polyaniline (PANI), poly (3,4-ethylenedioxythiophene) (PEDOT), polypyrrole, etc. ), [37][38][39][40][41][42][43] and viologens [44][45][46][47][48] . Anodic electrochromic materials refer to the chromic materials whose color change from transparent state to dark or opaque state when oxidized during the anodic polarization process.…”
Section: Electrochromic Materials Used For Smart Windowmentioning
confidence: 99%
“…π-conjugated polymers (CPs) and oligomers have attracted a great deal of interest due to their suitability for potential applications in supercapacitors [1,2], catalysts [3,4,5], actuators [6], polymer light-emitting diodes [7,8,9], electrochromic devices (ECDs) [10,11,12], polymer solar cells [13], and sensors [14,15,16]. The most commonly studied classes of CPs are poly(phenylene vinylene)s (PPV) [17], polycarbazoles (PCz) [18,19], polythiophenes (PT) [20], polypyrroles (PPy) [21], poly(3,4-ethylenedioxythiophene) (PEDOT) [22], and polyanilines (PANI) [23]. Cz-based polymers have been widely used as hole transporting and host materials in optoelectronic devices due to the nitrogen atom of Cz ring shows good hole transporting ability, high thermal stability, and ease of formation of radical cations and dications [24].…”
Section: Introductionmentioning
confidence: 99%